The dilemma in balancing involuntary e-leadership system for job satisfaction (Voices of employees at Dinas Perhubungan Kota Denpasar) - Dian Prabarini, Nyoman Sridiva (Review of Management, Accounting, and Business Studies, 2021)
E-leadership is a new style of leadership that uses technology as the main medium to communicate and move teams. Considering that technology is currently very developed, this becomes very easy and at the same time challenging because it needs to adapt and adjust to the workforce. The workforce needs to balance their work and life in order to work as optimally as possible and achieve the goals of the company. Work-life balance is one of the important factors that affect employee job satisfaction where the better the work-life balance, the higher the employee job satisfaction and vice versa. This research was conducted at Dinas Perhubungan Kota Denpasar. The number of respondents was 75 office employees, processed using SPSS. From the research results, it was found that e-leadership has a significant effect on job satisfaction, work-life balance has an insignificant effect on job satisfaction, also e-leadership and work-life balance have a significant effect on job satisfaction in Dinas Perhubungan Kota Denpasar.